Analisis Yuridis Pertanggungjawaban Pidana Pelaku dengan Gangguan Intelektual dalam Tindak Pidana Pencabulan Anak - Arisman Suar Bhakti Ibrahim; Dewi Yulinang; Aswad Karimali (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2026)
This study aims to analyze the criminal liability of perpetrators with intellectual disabilities in child molestation crimes according to Indonesian criminal law. The background of this study arises from the complexity of child molestation cases involving perpetrators with intellectual disabilities, where the ability to understand and control actions is an important factor in determining criminal liability. This study uses a normative legal method with a statutory and conceptual approach, and collects data through literature review from primary and secondary legal sources. The results of the study indicate that perpetrators with mild intellectual disabilities can still be held criminally responsible with certain considerations, while perpetrators with severe disabilities are more appropriately subject to treatment rather than criminal penalties. Article 44 of the Criminal Code serves as the primary basis in determining the perpetrator's liability status. This study emphasizes the importance of a balance between victim protection and fair treatment of perpetrators, as well as the involvement of experts in the legal process. The research findings emphasize that criminal law does not only focus on imposing sanctions, but also takes into account the perpetrator's condition so that justice can be achieved proportionally. The implications of this study are the need for clear guidelines for law enforcement and public education regarding intellectual disabilities to reduce negative stigma.